(untitled) - FAJAR WIGATI R, RR (LATERNE, 2014)
Speaking skills is one of the most important language skills to master students . Because of that, students can submit information. So that speaking ability can be mastered properly, therefore necessary textbooks in which there are exercises for speaking skills are needed. Kontakte Deutsch Extra is a textbook that contains German speaking skills training and therfore it is used for source of the data for this study. Formulation of the problem of this study is what kind of speaking exercise contained in Kontakte Deutsch Extra. The purpose of this study is to describe the types of exercises contained in Kontakte Deutsch Extra. Meanwhile, the research method used here is descriptive qualitative method. Data analysis was based on the theory of Speaking exercise from Heide (2006:43). From the data analysis it can be concluded that the type of exercise found in Kontakte Deutsch Extra is in form of Interview, Ketten?bungen (Exercise chain) and Bildgesteurte Übungen (exercise directed by the picture). Keywords: speaking exercise